1985
DOI: 10.1002/aja.1001730104
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal development of “Synaptic” ribbons and spherules in the guinea pig pineal gland

Abstract: Previous studies have shown that the functionally enigmatic pineal "synaptic" ribbons are structurally a heterogeneous group of organelles consisting of rodlike ribbons sensu stricto, spherules, and intermediate forms. As ribbons and spherules react differently under various experimental conditions, these organelles were studied qualitatively and quantitatively during the postnatal period in guinea pigs. It was found that the pinealocytes were highly differentiated at birth and contained all three forms of "sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1986
1986
1992
1992

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…True ribbon synapses were also seen in this study. Since they were not found in postnatal and adult guinea pig pineal glands (Banks et al, 1985; this study), but only in the embryonic stage, they may represent transitory structures. The synaptic nature of the "synaptic" ribbons in mammalian pineal glands may be lost during their development.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…True ribbon synapses were also seen in this study. Since they were not found in postnatal and adult guinea pig pineal glands (Banks et al, 1985; this study), but only in the embryonic stage, they may represent transitory structures. The synaptic nature of the "synaptic" ribbons in mammalian pineal glands may be lost during their development.…”
Section: Discussionmentioning
confidence: 54%
“…It was reported that the pineal "synaptic" ribbons appeared on day 4 postpartum in golden hamsters (Hewing, 1979) and on day 1 after delivery in rats (King and Doughtery, 1980). Recently, a n investigation of the postnatal development of "synaptic" ribbons in pineal glands of the Hartley strain of guinea pig revealed that SR, SS, and IMF were found in relatively high numbers in the pinealocytes of 1-hr newborn guinea pigs (Banks et al, 1985). That report indicates that "synaptic" ribbons may be present in prenatal pineal glands.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Note the diameter of SR,, is greater than the thickness of the SR, rod. 1984; Khaledpour and Vollrath, 1987;Diaz et al, ing ring-shaped and irregular-shaped SR (Matsushima 1990), which is seasonally dependent in some species et al, 1983a,b;Banks et al, 1985;Khaledpour and (Riemann et al, 1990), and respond differently to en- Vollrath, 1987). It is our opinion that many of these vironmental lighting (Vollrath, 1986) as well as to ex-intermediate forms represent SR, or SRFP cut in various ogenously applied indoles .…”
Section: Synaptic Ribbon Populations and Terminologymentioning
confidence: 99%